6-2x{2+2x[2+2x(2+a:2)-2]:16+0:2}=0
Răspunsuri la întrebare
Răspuns de
1
6-2*((2+2*(2+4+2a/4)-2))/16+0)=0
6-2*((2+2*(6+2a/8-2)/16=0
6-2*(2+12+4a/16-4)/16=0
6-2*(10+4a/16)/16=0
6-(20-8a/32)/16=0
(20-8a/32)/16=6
(20-8a/32)/16-6=0
20-8a/32-16*6=0
20-8a/32-96=0
20*32-8a-96=0
640-8a-96=0
544-8a=0
8a=544
a=544/8
a=68
6-2*((2+2*(6+2a/8-2)/16=0
6-2*(2+12+4a/16-4)/16=0
6-2*(10+4a/16)/16=0
6-(20-8a/32)/16=0
(20-8a/32)/16=6
(20-8a/32)/16-6=0
20-8a/32-16*6=0
20-8a/32-96=0
20*32-8a-96=0
640-8a-96=0
544-8a=0
8a=544
a=544/8
a=68
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă